2016
DOI: 10.1111/ane.12562
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for the treatment of mesial temporal lobe epilepsy

Abstract: Our findings indicate that RS may have similar or slightly less efficacy in some patients compared with invasive surgery. Randomized controlled trials of both treatment regimens should be undertaken to generate an evidence base for patient decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
(101 reference statements)
0
16
0
Order By: Relevance
“…Indeed, Régis et al ’s small multicentre European study using single fraction gamma knife in patients with hippocampal sclerosis who had similarly decided against conventional surgery—which was towards the end of recruitment when our patient received her treatment—reported transient increases in seizure activity in all patients after 9–12 months before a universal decrease, with overall seizure freedom in 65% at 2 years 2. A recent meta-analysis of radiosurgery techniques (X-rays or gamma radiation) in patients with hippocampal sclerosis not offered open surgery found this group’s seizure freedom rates were almost as good as with temporal lobe resection, albeit after a 14-month mean delay 3. However, there are no randomised clinical trials directly comparing efficacy and side effect profiles of invasive versus non-invasive surgical methods.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, Régis et al ’s small multicentre European study using single fraction gamma knife in patients with hippocampal sclerosis who had similarly decided against conventional surgery—which was towards the end of recruitment when our patient received her treatment—reported transient increases in seizure activity in all patients after 9–12 months before a universal decrease, with overall seizure freedom in 65% at 2 years 2. A recent meta-analysis of radiosurgery techniques (X-rays or gamma radiation) in patients with hippocampal sclerosis not offered open surgery found this group’s seizure freedom rates were almost as good as with temporal lobe resection, albeit after a 14-month mean delay 3. However, there are no randomised clinical trials directly comparing efficacy and side effect profiles of invasive versus non-invasive surgical methods.…”
Section: Discussionmentioning
confidence: 82%
“…In a retrospective medical record review of a subset of 68 patients enrolled in a large prospective observational study of epilepsy surgery, there were 0.04 hospitalizations per patient‐year in patients who were seizure‐free after ATL, compared to 0.25 hospitalizations per patient‐year among surgical and nonsurgical patients with persistent seizures . In a recent meta‐analysis, the pooled estimate of seizure‐free outcome after SRS was 51% (95% CI = 38%‐64%) . The most common AE was headache, which occurred in 9%‐85% of series in which it was reported (median = 43%).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of stereotactic radiosurgery for mesial temporal sclerosis [166] showed that the total number of patients reported remains low (<200) but that half became seizure free at a median of 14 months after treatment with a complication rate of around 8% (excluding headache which was more common) and rates of visual field defects similar to open surgery. MRI-guided laser thermocoagulation has been undertaken in a few patient with initially promising results.…”
Section: Epilepsy Surgerymentioning
confidence: 99%